PI-Based Set-Point Learning Control for Batch Processes with Unknown Dynamics and Nonrepetitive Uncertainties - Hao, Shoulin; Liu, Tao; Rogers, Eric; Wang, Youqing; Paszke, Wojciech (1975- )
For industrial batch processes with unknown dynamics subject to nonrepetitive initial conditions and disturbances, this paper proposes a novel adaptive data-driven set-point learning control (ADDSPLC) scheme based on only the measured process input and output data, which has two loops, one each for the dynamics within a batch and the other for the batchto-batch dynamics.
Keywords: batch processes with unknown dynamics; data-driven control; PI controller tuning; set-point learning control; robust convergence analysis; iterative extended state observer